Aunt Fanny's star : children and the loss of a loved one - Weninger, Brigitte (minedition, 2017)
When Aunt Fanny becomes too ill to look after herself, Mama Bunny decides to move her in with her family. This means big changes at the Bunny house, of course, but it also means fun and discovery for the three young bunnies as they get to learn all about their funny aunt. She shows them that there is always comfort and consolation in the twinkling stars overhead. This touching, gentle picture book helps children navigate the difficult issues of dealing with the death of a loved one. It shares in simple terms the truth that death affects us all, and that life goes on as surely as there are stars twinkling in the sky.